Metodologia de construç\~ao do painel dos agentes públicos das administraç\~oes estaduais e do distrito federal de 2014 a 2019 - Claudio Hamilton Matos Dos Santos; Diogo Moreira Chaves Cavalcante; André José Silva Brito; Udson Eduardo Nogueira Machado (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– This text details the technical procedures used in the construction of a panel data base of public servants and employees and military personnel working in the public administrations of Brazilian States. Six sets of procedures are presented. The first set deals with the extraction of the raw data on public servants and employees and military personnel of Brazilian States in the Relaç\~ao Anual das Informaç\~oes Sociais (Rais) database. The second deals with pairings of Rais data with the data available in the States's Transparency Portals. The third deals with imputations based on longitudinal analyses. The fourth deals with comparisons with data from alternative databases. The fifth deals with the estimation of the number of years each public servant/employee or member of the States military worked in the formal sector before getting their current jobs. Finally, the sixth deals with how the database itself is presented in R format.
Keywords: C55; H11; J45; M5; 330; the structure of public administration; public servants; military personnel; state public administration; panel data